Theranostics; Application of Nanosystems for Simultaneous Targeted Therapy and Imaging in Diseases - Pedram Torabian; Vahid Erfani-Moghadam (Jorjani Biomedicine Journal, 2016)
For decades, researchers have tried to develop non-invasive mechanisms for monitoring pathological conditions within the body of patients. Emerging nanotechnology enabled us to reach this aim. Scale of nano has the potential to increase early detection of pathological conditions among abnormal cells before diseased tissue or tumor development can be considerable which is helpful in disease treatment. In recent years, “Theranostics” has been emerged as a novel nano approach which performs diagnostic detection, therapy and follows up simultaneously. Therefore, Theranostics can be considered as an appropriate therapeutic approach for personalized medicine, pharmacogenomics and molecular imaging which can open a gate to develop novel therapies. Additionally, with a deeper molecular understanding, choosing drugs that are more effective will be possible. Finally, researchers believe that Theranostics has the potential to monitor treatments by increasing drug effectiveness and preventing inappropriate treatments and consequently reducing the cost of national health burden. In this review, structure and some applications of Theranostics and nano drug delivery systems have been discussed briefly.